Reading and Spelling Development Across Languages Varying in Orthographic Consistency: Do Their Paths Cross?. Issue 2 (25th January 2019) - Georgiou, George K.; Torppa, Minna; Landerl, Karin; Desrochers, Alain; Manolitsis, George; de Jong, Peter F.; Parrila, Rauno
Abstract : We examined the cross‐lagged relations between reading and spelling in five alphabetic orthographies varying in consistency (English, French, Dutch, German, and Greek). Nine hundred and forty‐one children were followed from Grade 1 to Grade 2 and were tested on word and pseudoword reading fluency and on spelling to dictation. Results indicated that the relations across languages were unidirectional: Earlier reading predicted subsequent spelling. However, we also found significant differences between languages in the strength of the effects of earlier reading on subsequent spelling. These findings suggest that, once children master decoding, the observed differences between languages are not related to the direction of the effects but to the strength of the effects from reading to spelling. Theoretical and practical implications are discussed.